The Influence of Photo‐Induced Space Charge and Energetic Disorder on the Indoor and Outdoor Performance of Organic Solar Cells. Issue 3 (11th February 2021) - Beuel, Sebastian; Hartnagel, Paula; Kirchartz, Thomas
Abstract: Apart from traditional large‐scale outdoor application, organic solar cells are also of interest for powering small, off‐grid electronic devices indoors. For operation under the low light intensities that are typical for indoor application, a high shunt resistance is required calling for thick active layers in industrial processing to ensure maximum coverage. However, the thickness of an organic solar cell based on energetically disordered semiconductors is limited by space‐charge effects from charged shallow defects under nonuniform generation. While other sources of space charge such as doping and asymmetric transport have been extensively discussed in previous studies, this work offers a theoretical analysis of this photo‐induced space charge in shallow defects and visualizes how the space charge builds up with increasing light intensity with drift‐diffusion simulations. It is shown that the effect particularly deteriorates the performance of an organic solar cell with high active‐layer thickness and substantial energetic disorder. However, the simulations reveal that solar cells are less sensitive to these parameters under low light intensities due to a reduced density of photo‐induced space charge. Therefore, a wider range of material systems and absorber thicknesses can be viable for indoor applications than one may initially expect from testing under 1 sun illumination. Abstract : The operation of solar cells based on energetically disordered organic semiconductors with a thick absorber layer under outdoor conditions is limited by photo‐induced space‐charge effects. Numerical drift‐diffusion simulations visualize the built‐up of space charge with increasing light intensity and reveal that thick devices with high energetic disorder may still be viable candidates for indoor applications.